2023
DOI: 10.1302/2633-1462.42.bjo-2023-0002.r1
|View full text |Cite
|
Sign up to set email alerts
|

Higher knee survivorship in young patients with monocompartmental osteoarthritis and constitutional deformity treated by high tibial osteotomy then total knee arthroplasty compared to an early total knee arthroplasty

Abstract: Aims The use of high tibial osteotomy (HTO) to delay total knee arthroplasty (TKA) in young patients with osteoarthritis (OA) and constitutional deformity remains debated. The aim of this study was to compare the long-term outcomes of TKA after HTO compared to TKA without HTO, using the time from the index OA surgery as reference (HTO for the study group, TKA for the control group). Methods This was a case-control study of consecutive patients receiving a posterior-stabilized TKA for OA between 1996 and 2010 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Restoring the correct alignment of the lower limb reduces the overload on the affected compartment improving pain and function, slowing the deterioration of the knee, and delaying or avoiding the need for arthroplasty [9, 48]. A recent case‐control study demonstrated a reduced need for prosthetic revision in young patients treated with high tibial osteotomy and then with TKA compared to young patients treated with an early TKA [22]. Therefore, knee osteotomy should be considered as a treatment option to postpone TKA in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring the correct alignment of the lower limb reduces the overload on the affected compartment improving pain and function, slowing the deterioration of the knee, and delaying or avoiding the need for arthroplasty [9, 48]. A recent case‐control study demonstrated a reduced need for prosthetic revision in young patients treated with high tibial osteotomy and then with TKA compared to young patients treated with an early TKA [22]. Therefore, knee osteotomy should be considered as a treatment option to postpone TKA in these patients.…”
Section: Discussionmentioning
confidence: 99%